Slow Steaming and Its Impact on Fruit and Vegetable Exporters in Türkiye - Gökmen, Gökhan (Kocaeli Üniversitesi, 2024)
Containerization has transformed global shipping, offering a faster, more reliable, and cost-effective transportation option. However, the 2008 financial crisis disrupted the industry, leading container liners to adopt slow steaming—a strategy to cut fuel costs and manage overcapacity by reducing vessel speeds. This study examines the impact of slow steaming on Türkiye's fruit and vegetable exporters, whose perishable goods are highly sensitive to shipping delays. Using a mixed-method approach, this research begins with a quantitative analysis of container vessels serving Turkish ports, using the AIS data to assess their operating speeds. This is followed by qualitative interviews with key stakeholders, including an operations manager of a container liner. The author further interviewed fruit and vegetable shippers to understand the impact of slow steaming on their businesses. Findings indicate that while slow steaming helped reduce operational costs of the container liners, it introduced significant challenges for perishable goods exporters, with longer transit times affecting product quality and market competitiveness. Despite these difficulties, Türkiye's fruit and vegetable exports grew from $1.5 billion in 2010 to $3.1 billion in 2023, demonstrating resilience but also highlighting the critical importance of managing shipping delays effectively. This study contributes to the literature by exploring the effects of slow steaming on a vulnerable yet economically vital sector, offering insights for policymakers and industry stakeholders on balancing cost efficiency with the need for timely delivery in global trade.

Konteyner taşımacılığı, küresel taşımacılığa daha hızlı, güvenilir ve maliyet açısından daha uygun bir taşıma seçeneği sunmuştur. Ancak 2008 finansal krizi Denizcilik sektörünü sarsmış, konteyner hatlarının yakıt maliyetlerini düşürmek ve aşırı kapasiteyi yönetmek amacıyla gemi hızlarını azaltarak yavaş seyir stratejisini benimsemelerine yol açmıştır. Bu çalışma, yavaş seyrin, meyve ve sebze ihracatçıları üzerindeki etkisini incelemektedir. Karma bir yöntem yaklaşımı kullanılarak yapılan bu araştırma, Türkiye limanlarına hizmet veren konteyner gemilerinin hızlarını değerlendirmiştir. Çalışmada AIS verileri kullanılarak nicel bir analiz yapılmıştır. Ardından, bir konteyner hattının operasyon yöneticisi de dahil olmak üzere meyve ve sebze ihracatçılarıyla görüşmeler yapılmıştır. Bulgular, yavaş seyrin konteyner hatlarının operasyonel maliyetlerini düşürmeye yardımcı olurken, çabuk bozulan ürünlerin ihracatçıları için önemli zorluklar getirdiğini, uzayan transit sürelerinin ürün kalitesini ve pazar rekabetçiliğini olumsuz etkilediğini göstermiştir. Bu zorluklara rağmen, Türkiye'nin meyve ve sebze ihracatı 2010 yılında 1,5 milyar dolardan 2023'te 3,1 milyar dolara yükselerek dayanıklılığı ortaya koymuş, ancak aynı zamanda sevkiyat gecikmelerinin etkili bir şekilde yönetilmesinin kritik önemini vurgulamıştır. Bu çalışma, yavaş seyrin ekonomik açıdan önemli ancak savunmasız bir sektör üzerindeki etkilerini inceleyerek, maliyet etkinliği ile küresel ticarette zamanında teslimat gereksinimi arasındaki dengeyi sağlamaya yönelik olarak politika yapıcılara ve sektör paydaşlarına içgörüler sunarak literatüre katkıda bulunmaktadır.
Yavaş Seyirin Türkiye’deki Meyve ve Sebze İhracatçılarının Üzerindeki Etkisi
Keywords: Maritime Transportation and Freight Services; Deniz Taşımacılığı ve Nakliye Hizmetleri